Analisis Semiotik Roland Barhtes Pada Lagu dalam Album “Selamat Ulang Tahun” Karya Nadin Amizah - Utari Putri, Alicia; Fathurrahman, Irfai; Hariyadi, Ahmad (Saba Jaya Publisher, 2024)
This research aims to describe the semiotics of Roland Barthes in Nadin Amaziah's song in Nadin Amizah's album